(untitled) (Texas Journal of Medical Science, 2024)
Cubitus varus deformity complicating supracondylar fracture of humerus in children usually implies a malunion from inappropriate treatment of the fracture . The resulting deformity can be solved only by osteotomy ,since the deformity once established it will not correct by remodeling . A lot of controversy is still present regarding the best age of the child to perform the corrective osteotomy . Cosmetic appearance is the most common indication for osteotomy